ChemInform Abstract: Mercury Azides and the Azide of Millon′s Base. Issue 3 (21st January 2014) - Lund, Henrik; Oeckler, Oliver; Schroeder, Thorsten; Schulz, Axel; Villinger, Alexander
Abstract The synthesis of Millon′s base (III)/(V) and metastable β‐Hg(N3)2 (II) and their characterization by powder and single crystal XRD closes an open gap in azide chemistry.